(3GdMOGFbs - (3GdOQGRj GdHMQGf, GHf YUahQ, jhSa Hf CMeO Hf EHQGgje, J(B1186(3g`s
(3ChdgG (B:s
.. (3cJGH GdELGQI hGdHMK ajg jbY aj eWGdH CQHYI GdChd aj GdELGQI hGdYbO heG jJQJH Ydjg hGdcdGe aj Pdc jbY aj ehGVY CMOgG GdELGQI KGHJI HGdfU cJGHG hSfI hELeGY YdeGA GdNGUI hGdYGeI (B...s
(3BNQgG (B:s
... (3Cbhd dG jNai Cf SjGb GdQhGjI GdePchQI XGgQ aj Cf GYJQGa GdQLd HPdc GdeGd dPdc GdTNU GdPj SeGg djS dg CUd HGdcdjI hdgPG Cf GdQLd GdeSei de jbHV GdeGd (B..s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8/215s
(3GdPQjYI (B6/1557s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis